Diversity of medicinal plants used for skincare by Bulungan tribe in North Kalimantan, Indonesia and its melanin biosynthesis inhibition (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kartina, Batubara I, Kuspradini H, Kusuma IW, Wahyuni WT, Egra S, Matsunaga T. 2022. Diversity of medicinal plants used for skincare by Bulungan tribe in North Kalimantan, Indonesia and its melanin biosynthesis inhibition. Biodiversitas 23: 1246-1253. Indigenous people of the Bulungan tribe in North Kalimantan, Indonesia have been utilizing plants for health purposes, including for skincare such as preventing skin from being dark due to melanin production. This study aimed to evaluate the diversity of medicinal plants utilized by the Bulungan tribe for skincare and determine the melanin biosynthesis inhibition activity. Plants having medicinal uses were investigated through literature studies and interviews with the members of Bulungan tribe in Tanjung Palas Tengah Village. Melanin biosynthesis inhibition was determined by identifying the tyrosinase inhibition potential using commercial tyrosinase enzyme, while intracellular and extracellular melanin biosynthesis production activity was determined using B16 melanoma cells. The results showed at least 19 plant species that have medicinal uses, including for skincare, with some of them having the potential for melanogenesis, both in suppressing and producing melanin. We found a plant sample with melanin suppression potential on B16 melanoma cell, namely Jatropha curcas, at 6.2 µg/ml concentration, which could decrease extracellular melanin content by 18%. Tyrosinase activity with L-tyrosine showed that Cinnamomum burmannii (root) (IC50: 3.4 ?g/mL) showed an insignificant difference with kojic acid, which served as positive control by showing an inhibitory level of (IC50: 0.14 ?g/mL). Based on the data obtained, a pharmacological study is recommended to investigate melanin biosynthesis as a skin whitening agent. We believe that this study can become basic data to discover several active compounds in future studies.